On Nonlinear Galerkin Approximation (Journal of Computational Mathematics, 1997)
Nonlinear Galerkin methods are numerical schemes adapted well to the long time integration of evolution partial differential equations. The aim of this paper is to discuss such schemes for reaction diffusion equations. The convergence results are proved.